Divergent Selection on Dispersal Targets Chemosensory and Neuronal Genes in Tribolium castaneum - Michael D. Pointer; Will J. Nash; Lewis G. Spurgin; Mark McMullan; Simon Butler; David S. Richardson (Molecular Ecology, 2026)
Dispersal is key to the life history, ecology and evolution of many organisms and important in pest invasiveness. However, the genetic architecture underlying variation in dispersal behaviour remains poorly understood outside of a few model species. We investigated the genomic basis of dispersal using artificial selection on replicated lines of Tribolium castaneum , a flour beetle, an emergent model system and an economically important agricultural pest. Combining whole‐genome resequencing with population‐level genotype–phenotype association analysis, we identify nine genomic regions and 42 genes associated with selection on dispersal. Identified candidate genes were significantly enriched for functions related to neuronal structure and function, as well as chemosensory behaviour and mating, suggesting that variation in dispersal is mediated by neural and chemosensory pathways. Our results demonstrate that dispersal propensity has a polygenic basis and support an interaction between dispersal and mating ecology in this system. These findings contribute to a deeper understanding of the genetic mechanisms driving dispersal evolution and its role in shaping eco‐evolutionary dynamics.